Urgensi penanaman nilai Pancasila kepada siswa sekolah dasar guna memperbaiki moral bangsa - Saniyah, Rohmatur Robiatus (Maliki Interdisciplinary Journal, 2024)
School is a place for a person to gain knowledge to deal with life and the surrounding environment, therefore good education must be instilled from an early age. The importance of instilling Pancasila values in elementary school students in order to improve the nation’s morale in a very modern era and very rapid changes in globalization in the field of education. The values contained in Pancasila are the basic values that become a reference in everyday life. The results of this study are to create and develop the potential of superior students, the implementation of Pancasila values must begin when children are still at an early age and of course we cannot just educate if we want to create students who are noble, responsible, it is very important for us to teaches the values contained in each of the Pancasila precepts